2014
DOI: 10.4236/ojped.2014.44034
|View full text |Cite
|
Sign up to set email alerts
|

Double Incomplete Pyloromyotomy (A. Ezzat Technique): A New Technique for Infantile Hypertrophic Pyloric Stenosis: Preliminary Study

Abstract: Background-Purpose: The study aimed to see the outcome of Double Incomplete Pyloromyotomy as new technique for surgical management of infantile hypertrophic pyloric stenosis (IHPS). Methods: This study was conducted in pediatric surgery unite, Zagazig University Hospital, Egypt. Fifteen patients were included in this study (11 male and 4 female) with IHPS from January 2012 to January 2013. Under general anesthesia, two longitudinal separated incisions at different planes as pyloromyotomy. Results: Postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…Mortality after pyloromyotomy is less than 0.4 % in most major centers and when it occurs, it is usually from fluid and electrolyte depletion in infants presenting late, and inadequately corrected electrolyte problems before surgery [ 17 , 18 ]. The overall mortality rate in this study was reported to be 4.9 % which is higher than 3.6 and 2.3 % reported in a Ghanaian and Iranian studies [ 35 , 36 ], respectively. A high mortality rate of 6.7 % was reported by Caneiro [ 32 ] in Dar es Salaam, Tanzania.…”
Section: Discussioncontrasting
confidence: 74%
“…Mortality after pyloromyotomy is less than 0.4 % in most major centers and when it occurs, it is usually from fluid and electrolyte depletion in infants presenting late, and inadequately corrected electrolyte problems before surgery [ 17 , 18 ]. The overall mortality rate in this study was reported to be 4.9 % which is higher than 3.6 and 2.3 % reported in a Ghanaian and Iranian studies [ 35 , 36 ], respectively. A high mortality rate of 6.7 % was reported by Caneiro [ 32 ] in Dar es Salaam, Tanzania.…”
Section: Discussioncontrasting
confidence: 74%